2016
DOI: 10.1167/16.15.14
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of crosstalk in stereoscopic display systems used for vision research

Abstract: Studying binocular vision requires precise control over the stimuli presented to the left and right eyes. A popular technique is to segregate signals either temporally (frame interleaving), spectrally (using colored filters), or through light polarization. None of these segregation methods achieves perfect isolation, and so a degree of crosstalk is usually apparent, in which signals intended for one eye are faintly visible to the other eye. Previous studies have reported crosstalk values mostly for consumer-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 30 publications
(40 reference statements)
1
19
0
Order By: Relevance
“…The stereo image input was in top-down VGA format and was displayed in interleaved line stereo mode at a resolution of 1,920 3 1,080 p and a refresh rate of 60 Hz: the left-eye image was displayed in even scanlines, and the right-eye image was displayed in odd scanlines. Crosstalk levels for polarizing filter and passive goggle systems, such as the one we used are known to be low (luminance crosstalk: 1.14%, CI: [1.13, 1.15], contrast crosstalk: À0.04%, CI: [À0.28, 0.18]; Baker, Kaestner, & Gouws, 2016).…”
Section: Apparatusmentioning
confidence: 99%
“…The stereo image input was in top-down VGA format and was displayed in interleaved line stereo mode at a resolution of 1,920 3 1,080 p and a refresh rate of 60 Hz: the left-eye image was displayed in even scanlines, and the right-eye image was displayed in odd scanlines. Crosstalk levels for polarizing filter and passive goggle systems, such as the one we used are known to be low (luminance crosstalk: 1.14%, CI: [1.13, 1.15], contrast crosstalk: À0.04%, CI: [À0.28, 0.18]; Baker, Kaestner, & Gouws, 2016).…”
Section: Apparatusmentioning
confidence: 99%
“…23,25 Both Maeda et al 25 and Watanabe et al 26 used red/green anaglyphs, which have been demonstrated to be prone to cross talk. 38 Cross talk is a particular issue for IOVD stimuli where even small amounts of interocular leakage can permit an observer to solve the MID task almost perfectly. Maeda et al 25 report that observers received feedback on the correctness of each trial, 25 though Watanabe et al 26 do not mention whether feedback was used.…”
Section: Discussionmentioning
confidence: 99%
“…The Viewpixx3D has been independently demonstrated to have good temporal properties and limited cross talk for the presentation of stereoscopic stimuli, especially for the highcontrast, dynamic, and transient dot stimuli (see below) used here. 38,39…”
Section: Apparatusmentioning
confidence: 99%
“…Crosstalk does not cause ghosts in DRDSs or DRDCs but it does result in the appearance of monocular cues, which may be confounded with cyclopean perception. This problem is generally recognized by researchers (Baker et al, 2016), yet the techniques of proper calibration are often not published. A notable exception is a study by Mulligan (1986) who presented a mathematical model of perceived luminances of the dots in DRDS displays.…”
Section: Comparison To Previous Approachesmentioning
confidence: 99%